The Impact of Domestic Policy on Farmers’ Welfare and Maize Processing Industry in Indonesia - Sebayang, Veralianta Br.; Sinaga, Bonar M.; Harianto, Harianto; Kariyasa, I. Ketut (International Journal of Economics and Financial Issues, 2019)
Maize is a strategic commodity for Indonesia, besides being used as community consumption, it is also used as input for industries such as animal feed and food processing industries as well as inputs for independent farmers. Industrial maize is obtained from two sources, namely domestic and imported. This study aims to determine the impact of government policies on the welfare of farmers and maize processing industries in Indonesia. The welfare of farmers is measured by producer surplus and consumer surplus. Using the econometric approach with a simultaneous equation system model, the estimation technique used is two stages least squares (2SLS), a range of data series from 1985 to 2017. The analysis shows that the corn harvest area is negatively related to farm labor wages, urea fertilizer prices, working capital interest rates and significant statistically. The level of maize productivity is positively related to the amount of use of urea and hybrid seeds, while the number of composite seed uses actually decreases maize productivity. The scenario of subsidizing urea fertilizer prices and subsidizing hybrid seed prices, can increase farmers’ maize production, but does not improve the welfare of farmers, because the additional production produced by farmers is not able to be absorbed by the market and prices drop dramatically, but the policy scenario is economically efficient. While the scenario of increasing import tariffs can actually increase farmers’ welfare even though the overall policy is not efficient. The role of the government is very necessary especially in maintaining price stability when overproduction, this can be implemented by procuring maize by the government when overproduction, so prices remain stable. Keywords: hybrid seed, import tariff, maize production, urea fertilizer, welfare JEL Classification: Q17 DOI: https://doi.org/10.32479/ijefi.7910